Sericin cocoon bio-compatibilizer for reactive blending of thermoplastic cassava starch - Thanongsak Chaiyaso (Nature Portfolio, 2021)
Abstract Cassava starch was blended with glycerol to prepare thermoplastic starch (TPS). Thermoplastic starch was premixed with sericin (TPSS) by solution mixing and then melt-blended with polyethylene grafted maleic anhydride (PEMAH). The effect of sericin on the mechanical properties, morphology, thermal properties, rheology, and reaction mechanism was investigated. The tensile strength and elongation at break of the TPSS10/PEMAH blend were improved to 12.2 MPa and 100.4%, respectively. The TPS/PEMAH morphology presented polyethylene grafted maleic anhydride particles (2 μm) dispersed in the thermoplastic starch matrix, which decreased in size to approximately 200 nm when 5% sericin was used. The melting temperature of polyethylene grafted maleic anhydride (121 °C) decreased to 111 °C because of the small crystal size of the polyethylene grafted maleic anhydride phase. The viscosity of TPS/PEMAH increased with increasing sericin content because of the chain extension. Fourier-transform infrared spectroscopy confirmed the reaction between the amino groups of sericin and the maleic anhydride groups of polyethylene grafted maleic anhydride. This reaction reduced the interfacial tension between thermoplastic starch and polyethylene grafted maleic anhydride, which improved the compatibility, mechanical properties, and morphology of the blend.